If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -2x = 36 Solving 10 + -2x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -2x = 36 + -10 Combine like terms: 10 + -10 = 0 0 + -2x = 36 + -10 -2x = 36 + -10 Combine like terms: 36 + -10 = 26 -2x = 26 Divide each side by '-2'. x = -13 Simplifying x = -13
| 2.8*18.3=a | | (2x-5)(4x-1)=0 | | -11(1+8m)=-11(1+5m) | | 4(-5+2y)= | | 5x+9=-3x+1 | | -2(-2y+5)= | | u=6(3n+33)+7(n+1) | | -3-5k=2 | | 2.2*18.3=a | | 12+9x+2-5x=22 | | (y+2)+-6= | | (h+-3)+-6= | | -6+5x=8x-8 | | 2x+7=6x-11 | | 4(3)=12y | | -2(a+1)=2(a-3) | | (-7q)(-4)= | | 4x-20=2x+6 | | 3+6x+1=2x+25+x | | .23x-7=3 | | u=6n(3n+33)+7(n+1) | | 6a-4=4a+26 | | 9a+7=10(a-1)-4(1-5a) | | (3+2k)(-3)= | | =200+400+900-100 | | 4(3y)=12y | | 6=6n(3n+33)+7(n+1) | | 4a+26=6a-4 | | (3d+2)(-3)= | | -4r-1=27 | | (c+3)+4= | | =200+400 |